Reinvigorating the Desire to Teach: Teacher Professional Development for Creativity, Agency, Stress Reduction, and Wellbeing - Anderson, Ross C.; Katz-Buonincontro, Jen; Livie, Mari; Land, Jessica; Beard, Nathan; Bousselot, Tracy; Schuhe, Gabriella (Frontiers in Education, 2022)
Research suggests that teachers’ creative development may materialize in more resilience and joy and less stress, but these connections have received little attention. This mixed methods study analyzes the effectiveness of a hybrid professional development model focused on teachers’ creative agency during the COVID-19 pandemic, a period of intensified stress, anxiety, and disconnect. Results indicated the PD experience supported (a) an increase in teachers’ creative agency, empathy, joy, buoyancy, and support in teaching during the pandemic and (b) a reduction in their secondary traumatic stress. Qualitative analyses illustrated a variety of personalized pathways for this development. The evidence suggests teachers’ creative agency and well-being can develop through a complementary process, rooted in creativity and the arts.